Efektifitas Pemberian Intervensi Diabetes Self-Management Education (DSME) Berbasis Audiovisual Terhadap Pengetahuan dan Keterampilan Perawatan Diri Diabetes - Candra Citra Sari, Ni Made; Sagitarini, Putu Noviana; Sanjana, I Wayan Edi (STIKES Ngesti Waluyo, 2022)
The increasing incidence of complicated diseases in Bali could indicate that diabetes self-care is not optimal. Diabetes mellitus, also abbreviated as DM, is a non-communicable disease whose number of sufferers is increasing. This study aims to examine the effectiveness of audiovisual-based DSME on knowledge and skills of self-care for type 2 diabetes. The design of this study was quasi-experimental design with control group. The sample of the research were 76 respondents who were selected through purposive sampling technique, and then they were divided into two groups, namely the control group (38 respondents) and the intervention group of 38 respondents. Audiovisual-based DSME was given for 5 sessions, which was held 1 week per 1 session. Statistical results showed that there was a significant effect of audiovisual-based DSME on knowledge and skills of self-care for type 2 diabetes (p-value <0.05 for both knowledge and skills). This intervention can be used as an innovation in providing education for diabetes in improving self-care behavior and reducing the risk of complications in the midst of the COVID-19 pandemic.